Kidney transplant outcomes associated with the use of increased risk donors in children. Issue 6 (1st February 2019) - Kizilbash, Sarah J.; Rheault, Michelle N.; Wang, Qi; Vock, David M.; Chinnakotla, Srinath; Pruett, Tim; Chavers, Blanche M.
Abstract : Increased risk donors (IRDs) may inadvertently transmit blood‐borne viruses to organ recipients through transplant. Rates of IRD kidney transplants in children and the associated outcomes are unknown. We used the Scientific Registry of Transplant Recipients to identify pediatric deceased donor kidney transplants that were performed in the United States between January 1, 2005 and December 31, 2015. We used the Cox regression analysis to compare patient and graft survival between IRD and non‐IRD recipients, and a sequential Cox approach to evaluate survival benefit after IRD transplants compared with remaining on the waitlist and never accepting an IRD kidney. We studied 328 recipients with and 4850 without IRD transplants. The annual IRD transplant rates ranged from 3.4% to 13.2%. IRDs were more likely to be male ( P  = .04), black ( P  < .001), and die from head trauma ( P  = .006). IRD recipients had higher mean cPRA (0.085 vs 0.065, P  = .02). After multivariate adjustment, patient survival after IRD transplants was significantly higher compared with remaining on the waitlist (adjusted hazard ratio [aHR]: 0.48, 95% CI: 0.26‐0.88, P  = .018); however, patient (aHR: 0.93, 95% CI: 0.54‐1.59, P  = .79) and graft survival (aHR: 0.89, 95% CI: 0.70‐1.13, P  = .32) were similar between IRD and non‐IRD recipients. We recommend that IRDs be considered for transplant in children. Abstract : Kizilbash et al find superior patient survival in pediatric kidney transplant recipients who receive an organ from an increased risk donor compared to remaining on the waitlist, as well as similar patient and graft survival compared with standard criteria donors.